Investigation of the dislocation structure in Czochralski germanium crystals grown in [211] and [110] growth directions. Issue 23 (21st May 2021) - Gradwohl, Kevin-P.; Roder, Melissa; Danilewsky, Andreas N.; Sumathi, R. Radhakrishnan
Abstract : X-ray topography of the [211] Ge crystal grown by the Cz-method shows that dislocations can be confined within the (1̄11) glide plane. Abstract : The dislocation structure of single-crystalline germanium crystals grown by the Czochralski method in [2 1 1] and [1 1 0] directions has been examined by white beam X-ray topography. The dislocation densities in different parts of the crystals ranged from around 40 to 4000 cm −2 . It was demonstrated that utilizing a well-executed Dash necking procedure with high growth speeds in growth directions parallel to a dislocation glide plane leads to the selection of dislocation line and type. Dislocations in the [2 1 1] crystal were mainly oriented in the [1 0 1] and [1 1 0] directions and hence confined within the (1̄ 1 1) glide plane. A comprehensive Burgers vector analysis revealed that they were predominantly screw dislocations. The dislocation lines in the [1 1 0] crystal were mostly aligned to the [0 1 1̄], [1 0 1̄], and [1 0 1] orientations, within the (1̄ 1 1) and (11̄1) glide planes and predominantly 60° dislocations.